Effects of energetic particles on the density-gradient-driven collisionless trapped electron mode instability in tokamak plasmas. (25th May 2021) - Hussain, M S; Guo, Weixin; Wang, Lu
Abstract: We investigate analytically the effects of energetic particles (EPs) on the instability of the density-gradient-driven collisionless trapped electron mode (CTEM) through linear gyrokinetic theory and bounce kinetic theory in tokamak plasmas. The effects of EPs, including fusion-born alpha particles and neutral-beam-injection-driven beam ions, on the CTEM instability are compared for the dynamic model with slowing-down (SD) and equivalent Maxwellian (EM) equilibrium EP distribution functions and dilution model. It is found that the density-gradient-driven CTEM instability in the long wavelength regime can be further destabilized by EPs mainly due to the downshift in the real frequency of the mode by dilution effects. This is attributed to more resonant electrons around the smaller phase velocity of the drift wave and the consequent stronger excitation of CTEM instability. The growth rate is slightly higher for the dilution model as compared to that for the dynamic model since the Landau damping effects of EPs are neglected in the dilution model. Moreover, there is no significant difference in the growth rate between the cases of SD and EM equilibrium EP distribution functions, except for the case of alpha particles and with relatively higher electron temperature.